2021
DOI: 10.3390/diagnostics11030434
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Complement Factors in Patients with Periprosthetic Joint Infection after Undergoing Revision Arthroplasty of the Hip or Knee Joint

Abstract: The role and diagnostic value of the synovial complement system in patients with low-grade periprosthetic joint infection (PJI) are unclear. We sought to evaluate, for the first time, the usefulness of synovial complement factors in these patients by measuring the individual synovial fluid levels of complement factors (C1q, C3b/iC3b, C4b, C5, C5a, C9, factor B, factor D, factor H, factor I, properdin, and mannose-binding lectin [MBL]). The patients (n = 74) were classified into septic (n = 28) and aseptic (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Loosening of the prosthesis after hip arthroplasty often causes pain, resulting in limited walking and thus disuse osteoporosis (21)(22)(23). Revision hip arthroplasty has high risks and a number of variables, making it a difficult operation in joint surgery (24).…”
Section: Discussionmentioning
confidence: 99%
“…Loosening of the prosthesis after hip arthroplasty often causes pain, resulting in limited walking and thus disuse osteoporosis (21)(22)(23). Revision hip arthroplasty has high risks and a number of variables, making it a difficult operation in joint surgery (24).…”
Section: Discussionmentioning
confidence: 99%
“…A jelenleg ismert biomarkerek nem alkalmazhatók egyedüli vizsgálatként a periprotetikus infekció diagnózisának felállításában, de kérdéses, hogy létezik-e olyan biomarker, amely egyedüli szereplőként biztos választ adhat erre a nehezen eldönthető kérdésre. Fröschen és mtsai közleményükben arra utalnak, hogy érdemes lehet gondolkodásmódot váltani és az "egy legjobb biomarker" kiválasztása helyett a gyulladásos folyamat megismerésére helyezni a fókuszt és abból meghatározni egy jellemző listát [35]. Ez a gondolkodás főként a krónikus, bizonytalan panaszokat okozó periprotetikus infekció esetében lehet fontos.…”
Section: Megbeszélésunclassified
“…102 The complement system, part of the innate immune response, is organized into a cascading hierarchy through three pathwaysclassical, alternative, and lectin, which leads to the generation of a MAC complex and lysing of target cells. 103 Complement factors involved in all three pathways including C1q, Cb3, C4b, C5, C5a, C9, B, D, H, I, and MBL are all upregulated in PJI-diagnosed synovial samples compared with aseptic cohorts 104 (Figure 1). Fisher et al 105 reported a technique using the CIBERSORTx transcriptomic-based cellular deconvolution tool that uses RNA extracted from synovial fluid to create a cellular profile with predictive power for PJI when changes in granulocyte, total macrophage/monocyte, M0 macrophages, and M2 macrophages are selectively increased.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…The complement system, part of the innate immune response, is organized into a cascading hierarchy through three pathways—classical, alternative, and lectin, which leads to the generation of a MAC complex and lysing of target cells 103 . Complement factors involved in all three pathways including C1q, Cb3, C4b, C5, C5a, C9, B, D, H, I, and MBL are all upregulated in PJI‐diagnosed synovial samples compared with aseptic cohorts 104 (Figure 1).…”
Section: Transcriptomics and Proteomics–biomarkersmentioning
confidence: 99%